Novel stem/progenitor cells with neuronal differentiation potential reside in the leptomeningeal niche - Bifari, Francesco (J Cell Mol Med, 2009)
Stem cells capable of generating neural differentiated cells are recognized by the expression of nestin and reside in specific regions of the brain, namely, hippocampus, subventricular zone and olfactory bulb. For other brain structures, such as leptomeninges, which contribute to the correct cortex development and functions, there is no evidence so far that they may contain stem/precursor cells. In this work, we show for the first time that nestin-positive cells are present in rat leptomeninges during development up to adulthood. The newly identified nestin-positive cells can be extracted and expanded in vitro both as neurospheres, displaying high similarity with subventricular zone–derived neural stem cells, and as homogeneous cell population with stem cell features. In vitro expanded stem cell population can differentiate with high efficiency into excitable cells with neuronal phenotype and morphology. Once injected into the adult brain, these cells survive and differentiate into neurons, thus showing that their neuronal differentiation potential is operational also in vivo. In conclusion, our data provide evidence that a specific population of immature cells endowed of neuronal differentiation potential is resident in the leptomeninges throughout the life. As leptomeninges cover the entire central nervous system, these findings could have relevant implications for studies on cortical development and for regenerative medicine applied to neurological disorders.